Kinematic analysis of the kick start underwater phase of young male swimmers - Wadrzyk, L.; Staszkiewicz, R. (Journal of Kinesiology and Exercise Sciences, 2018)
Introduction: The introduction of a starting block with an adjustable and slanted footrest has caused the development of a new starting technique - the Kick Start. Therefore, research on swim start seems necessary, particularly concerning the Kick Start underwater phase. Aim: The study aim was to characterise the underwater phase of the Kick Start among young, male, competitive swimmers. Basic procedures. The study included 32 male, youth, competitive swimmers (mean age=16.61 years, height=1.80 m, body mass=72.47 kg, FINA Points=617). Participants executed three freestyle Kick Starts recorded using an underwater high-speed camera. Videos were kinematically analysed using the Skill Spector programme. Then, k-means clustering was applied. Results. Participants were classified into three clusters. Cluster FT ("flat trajectory") comprised swimmers with a "flat" course of underwater movement - low value of the angle of water attack (KA=0.92o), maximum depth of the head (hmax=0.85 m), distance (dmax=0.71 m), and time to maximum depth of the head (tmax=0.51 s). Group MT ("moderate trajectory") had moderate values of the above-mentioned parameters (KA=10.27o, hmax=0.93 m, dmax=1.03 m, tmax=0.60 s), while Cluster DT ("deep trajectory") achieved the highest values (KA=15.74o, hmax=1.05 m, dmax=1.38 m, tmax=0.73 s). The time to reach 15 m in Cluster FT was about 0.3 s slower than in Group MT and DT, although this dissimilarity was not significant. Conclusions. The course of underwater movement is mostly affected by the angle at which swimmers submerge. There is no "ideal" way to perform the underwater phase, however, it should not be executed too close to the water surface.